The Influence of Regional Original Income, General Allocation Funds, and Budget Surplus Calculations on Regional Expenditures of Regencies/Cities in Bengkulu Province - Imas Khairunisa; Maria; Indriani Indah Astuti (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Surplus Budget (SiLPA) on Regional Expenditure in Regencies/Cities in Bengkulu Province for the 2019-2023 period. This study uses secondary data obtained from the Budget Realization Report (LRA) of local governments sourced from the Supreme Audit Agency of the Republic of Indonesia (BPK RI) with a sample of 10 Regencies/Cities in Bengkulu Province. The research method used is a quantitative approach with multiple linear regression analysis techniques to examine the relationship between variables. The results show that PAD has a negative and significant effect on regional expenditure, DAU has a positive and significant effect, while SiLPA has no significant effect. This finding indicates the existence of the Flypaper Effect phenomenon, where central transfer funds influence expenditure more than regional original revenue.